1991
DOI: 10.1073/pnas.88.24.10988
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of exfoliated human cervical cells: evidence of extensive structural changes during carcinogenesis.

Abstract: AJISTRACTInfrared spectra were obtained from exfoliated cervical cells from 156 females, of whom 136 were normal, 12-had cervical cancer, and 8 had dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
208
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(219 citation statements)
references
References 12 publications
10
208
1
Order By: Relevance
“…This is in agreement with earlier studies [26,27,30] on exfoliated cervical cells, which correlated abnormality with an observed increase in the intensity of phosphodiester vibrations. In general, these bands appear more intense than the methyl and methylene deformation modes (1450-1350 cm −1 ) in areas of high-grade dysplasia in all samples investigated in this study.…”
Section: Ectocervical Epitheliumsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with earlier studies [26,27,30] on exfoliated cervical cells, which correlated abnormality with an observed increase in the intensity of phosphodiester vibrations. In general, these bands appear more intense than the methyl and methylene deformation modes (1450-1350 cm −1 ) in areas of high-grade dysplasia in all samples investigated in this study.…”
Section: Ectocervical Epitheliumsupporting
confidence: 93%
“…Several comprehensive books and articles outline the field [22][23][24][25]. One area that has received considerable attention was the application of the FTIR technique to the diagnosis of cervical neoplasia [26][27][28][29][30][31][32][33][34][35]. Early studies reported spectral differences between exfoliated cells from patients diagnosed normal and dysplastic by cytological [26,27] and histological methods [28,30].…”
Section: The Infrared Alternativementioning
confidence: 99%
“…The changes in the intensity of the shoulder around 1465 cm −1 are more pronounced in the imatinib-resistant K562 cells upon ponatinib introduction. The bands at 1239 and 1086 cm −1 are of nucleic acids and attributed to PO 2 − asymmetric and symmetric stretch [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the above mentioned bands, there are some of those present in the spectrum of the pure enzyme, such as the two signals at 1450 cm -1 and 1490 cm -1 assigned to the scissor vibrations of ≡C-H groups and a signal at 2920 cm -1 generated by the C-H symmetric stretching vibrations of -CH 2 and -CH 3 groups. Also, the most important and characteristic for the pure enzymes are the amide I and amide II bands seen at 1645 cm -1 and 1542 cm -1 respectively [32,33]. Afer the immobilization, those bands were not only noticed to have their intensities decreased, but also their wave numbers (cm -1 ) slightly shifted to 1637 and 1536 cm -1 , respectively.…”
Section: Evaluation Of the Hydrolytic Activity Ofmentioning
confidence: 99%